Current trends in materials engineering II : selected, peer reviewed papers from the 25th Scientific Conference of the Microscopy Society Malaysia (25th SCMSM 2016), December 7-9, 2016, Bangi, Selangor, Malaysia - Jaafar, Mariatti; Lockman, Zainovia (Trans Tech Publications Ltd., 2017)
This book is a compilation of selected papers presented during the 25th Scientific Conference Microscopy Society Malaysia held in Bangi, Malaysia on 7th to the 9th of December 2016. This book shows the key role of microscopy and other various analytical techniques in the modern materials science including for the research of metals, ceramics, polymers, composites, nanomaterials and biomaterials. All contributions in this book concentrated around materials with properties and applications that may aid in solving pressing global issues such as environment, pollution, energy and biomedicine. Scanning Electron Microscopy, Atomic Force Microscopy, Transmission Electron Microscopy, Nanomaterials, Polymers, Composites, Semiconductors, Metals, Alloys, Ceramics, Corrosion, Biomaterials Materials Science.